Library Networks in India -An Overview - Murthy, S.S. (DESIDOC Journal of Library & Information Technology, 2002)
This paper gives an overview of the development of library networks in India. It also mentions the efforts made by the Planning Commission, Government of India, to promote resource sharing among libraries in the country. The present scenario of library networking is also briefly presented. The main problems in early operationalising the library networks include retro-conversion of holdings data, non-availability of suitable software for operating large databases and online searching in a wide-area-network mode at prices affordable by all the libraries, lack of adequate standardisation and non-availability of adequate training facilities to cover all the. Library staff participating in the network programmes. Some possible solutions to these problems are suggested. http://dx.doi.org/10.14429/dbit.16.2.3250